A Disproportionality Analysis of β‐lactam Antibiotic Related Blood and Lymphatic System Disorders Based on the FDA Adverse Event Reporting System Database - Jing Liu; Min Zhang; Zongwei Tang; Xiaoxiao Wang; Li Mu; Wanyi Chen; Haichi Song (Health Science Reports, 2026)
ABSTRACT Background and Aims β‐lactam antibiotics stand as the most profoundly impactful classes of antibacterial agents worldwide. Their widespread application has raised safety concerns over adverse events (AEs), such as blood and lymphatic system disorders (BLSDs). This study systematically evaluated and compared BLSDs associated with β‐lactam antibiotics based on real‐world data. Methods We reviewed the FDA Adverse Event Reporting System (FAERS) database from 2004Q1 to 2025Q1. To explore the associations between 30 FDA‐approved β‐lactam antibiotics and BLSDs, 4 disproportionality analysis algorithms were utilized, including reporting odds ratio, proportional reporting ratio, bayesian confidence propagation neural network, and multi‐item gamma poisson shrinker. Our analytical framework included subgroup analysis and sensitivity analysis, with the Weibull distribution applied to model the pattern of BLSDs over time. Results The total number of reported BLSDs was 7872, accounting for 6.93% of all AEs related to β‐lactam antibiotics. Notably, piperacillin/tazobactam, ceftriaxone, meropenem, cefazolin, cefepime, ceftazidime, ampicillin, oxacillin, cefotetan, and piperacillin produced strong signals of disproportionate reporting for BLSDs. Pyrexia, rash, and acute kidney injury emerged as the most frequently reported concurrent AEs. At the designated medical event level, several β‐lactam antibiotics were found to be associated with agranulocytosis, hemolytic anemia, immune thrombocytopenia, pancytopenia, and other hematological AEs. With respect to the time‐to‐onset patterns, ceftriaxone, meropenem, and ceftazidime were classified as early failure modes, whereas cefepime, cefotetan, oxacillin, and piperacillin were categorized as wearout failure modes. Conclusions This study revealed a notable association between β‐lactam antibiotics and BLSDs, underscoring the importance of blood tests in clinical practice when β‐lactam antibiotics are prescribed.